Arachidonic acid, a clinically adverse mediator in the ovarian cancer microenvironment, impairs JAK‐STAT signaling in macrophages by perturbing lipid raft structures. Issue 17 (4th May 2022) - Hammoud, Mohamad K.; Dietze, Raimund; Pesek, Jelena; Finkernagel, Florian; Unger, Annika; Bieringer, Tim; Nist, Andrea; Stiewe, Thorsten; Bhagwat, Aditya M.; Nockher, Wolfgang Andreas; Reinartz, Silke; Müller‐Brüsselbach, Sabine; et al.
Abstract : Survival of ovarian carcinoma is associated with the abundance of immunosuppressed CD163 high CD206 high tumor‐associated macrophages (TAMs) and high levels of arachidonic acid (AA) in the tumor microenvironment. Here, we show that both associations are functionally linked. Transcriptional profiling revealed that high CD163 and CD206/MRC1 expression in TAMs is strongly associated with an inhibition of cytokine‐triggered signaling, mirrored by an impaired transcriptional response to interferons and IL‐6 in monocyte‐derived macrophages by AA. This inhibition of pro‐inflammatory signaling is caused by dysfunctions of the cognate receptors, indicated by the inhibition of JAK1, JAK2, STAT1, and STAT3 phosphorylation, and by the displacement of the interferon receptor IFNAR1, STAT1 and other immune‐regulatory proteins from lipid rafts. AA exposure led to a dramatic accumulation of free AA in lipid rafts, which appears to be mechanistically crucial, as the inhibition of its incorporation into phospholipids did not affect the AA‐mediated interference with STAT1 phosphorylation. Inhibition of interferon‐triggered STAT1 phosphorylation by AA was reversed by water‐soluble cholesterol, known to prevent the perturbation of lipid raft structure by AA. These findings suggest that the pharmacologic restoration of lipid raft functions in TAMs may contribute to the development new therapeutic approaches. Abstract : This study shows that the clinically adverse abundance of immunocompromised macrophages and arachidonic acid (AA) in the ovarian carcinoma microenvironment (TME) are functionally linked. AA impairs transcriptional signalling via JAK/STAT‐dependent cytokine receptors by counteracting compartmentalization of receptor and STAT proteins into lipid rafts. Inhibition of STAT signalling is reversible by protecting lipid raft structure with water‐soluble cholesterol, pointing to potential therapeutic applications.